From Exclusion to Equality: Realizing the rights of persons with disabilities - Sha Zukang, Louise Arbour; Anders B. Johnsson (2007)
Handbook for Parliamentarians on the Convention on the Rights of Persons with Disabilities and its Optional Protocol